Multivariate Cointegration and Causality between Exports, Electricity Consumption and Real Income per Capita: Recent Evidence from Japan - Sami, Janesh (International Journal of Energy Economics and Policy, 2011)
The current literature on the relationship between electricity, exports and economic growth is mixed. This paper examines the relationship between exports, electricity consumption and real income per capita in Japan using time series data from 1960-2007.We applied bounds testing procedure developed by Pesaran et al., (2001) and found that there is cointegrating relationship between electricity consumption ,exports and economic growth. On establishing cointegration, the causal relationship electricity consumption, exports and economic investigation was investigated within a Vector Error Correction Model (VECM) framework. We found that in the long run, there is causality from exports and real GDP per capita to electricity consumption. Keywords: Exports; Electricity consumption; Real Income per capita; Japan JEL Classifications: Q43; C32